Dysregulation of Nrf2 in hepatocellular carcinoma: Role in cancer progression and chemoresistance - Raghunath, A.; Sundarraj, K.; Arfuso, Frank; Sethi, G.; Perumal, E. (MDPI AG, 2018)
The liver executes versatile functions and is the chief organ for metabolism of toxicants/xenobiotics. Hepatocellular carcinoma (HCC) is the most common primary liver malignancy and the third foremost cause of cancer death worldwide. Oxidative stress is a key factor related with the development and progression of HCC. Nuclear factor erythroid 2 [NF-E2]-related factor 2 (Nrf2) is a cytosolic transcription factor, which regulates redox homeostasis by activating the expression of an array of antioxidant response element-dependent genes. Nrf2 displays conflicting roles in normal, healthy liver and HCC; in the former, Nrf2 offers beneficial effects, whereas in the latter it causes detrimental effects favouring the proliferation and survival of HCC. Sustained Nrf2 activation has been observed in HCC and facilitates its progression and aggressiveness. This review summarizes the role and mechanism(s) of action of Nrf2 dysregulation in HCC and therapeutic options that can be employed to modulate this transcription factor.